ANALISIS PENERAPAN ACTIVITY-BASED COSTING DALAM PENENTUAN HARGA POKOK PRODUKSI PADA UMKM MANUFAKTUR DI KABUPATEN BANDUNG BARAT - Asep Irpan Nugraha; Abdul Halim; Yudi Subarkah; Oleh Oleh; Wiwik Dyah (Institut Penelitian Matematika, Komputer, Keperawatan, Pendidikan dan Ekonomi (IPM2KPE), 2026)
This study aims to analyze the implementation of the Activity-Based Costing (ABC) method in determining the cost of production in manufacturing micro, small, and medium-sized enterprises (MSMEs) in West Bandung Regency and to compare its results with those of the traditional costing method currently applied. Accurate determination of production costs is essential for setting competitive selling prices, improving profitability, and supporting effective cost control. This study employed a descriptive qualitative approach with a case study design. Data were collected through direct observation of production processes, in-depth interviews with business owners, finance personnel, and production staff, as well as documentation of production cost records. The collected data were analyzed by identifying production activities, classifying costs into activity cost pools, determining appropriate cost drivers, and calculating product costs using the ABC method before comparing them with the traditional costing results. The findings reveal that the traditional costing method tends to allocate overhead costs uniformly, leading to cost distortion, particularly for low-volume and high-complexity products. In contrast, the ABC method allocates indirect costs based on actual resource consumption, resulting in more accurate and representative product cost information. The improved cost accuracy enables MSMEs to establish more competitive pricing strategies, evaluate product profitability more effectively, and make better-informed managerial decisions. The study concludes that the implementation of ABC can enhance the reliability of production cost information and improve operational efficiency. Therefore, manufacturing MSMEs are encouraged to gradually adopt the ABC method, strengthen production cost recording systems, and enhance managerial competencies through cost accounting training.